Neo-Nazi Heteroactivism and the Swedish Nationalist Contradiction - Lagerman, Julia (ACME, 2023)
This article is about one of the most violent and visible form anti-LGBTQI activism in Sweden, conducted by Neo-Nazis. Through a critical discourse analysis of 189 texts published in Swedish newspapers and Neo-Nazi alternative media, it argues that contemporary Swedish Neo-Nazi anti-LGBTQI activism draws upon and constructs transnational heteroactivist discourses. They claim to “protect the nuclear family” to deflate accusations of homophobia while gaining substantial visibility through news media covering their actions. The findings demonstrate the three ways Neo-Nazi texts use heteroactivist strategies. First, the texts argue that LGBTQI rights and feminism are societally harmful.  Second, through intertextuality they refer to both local and international alternative media as the basis for their arguments. Third, they rationalise homophobic hatred. This paper contributes to discussions of heteroactivism, revealing the need to grapple with the ways it is intertwined with race and nationalism. Empirically, the analysis also highlights the significance of anti-LGBTQI activism in contemporary white power and extreme-right movements. The inclusion of news media texts that frame and represent heteroactivist strategies reveals that, despite their rationalising efforts, Neo-Nazi anti-LGBTQI activism is represented as homophobic and hateful in news and debate articles describing them. Additionally, news media representations of Neo-Nazi heteroactivist discourse present a nationalist contradiction, with authors re-constructing narratives of Sweden as a “LGBT friendly nation”, bringing to light complex relations between heteroactivism, homophobia, racism, and nationalism.